What we can learn from college reform in the EU - JACQUELINE KRESS (Academic Chairpersons Conference Proceedings, 2019)
The Bologna Process—a curriculum reform encompassing 48 EU countries—engages faculty by discipline to articulate what students should be able to know, do, and understand at each degree level through academic dialogue. This session overviews its mechanisms and challenges and provides guidance for applying its lessons at US institutions.
Keywords: Bologna Process; curriculum renewal; assessment; data-based decisions; outcomes; alignment